2022
DOI: 10.1039/d2ce00942k
|View full text |Cite
|
Sign up to set email alerts
|

Rationalising the difference in crystallisability of two sulflowers using efficient in silico methods

Abstract: The molecular structures of the first and second generation Sulflowers, Sulflower and Persulfurated Coronene (PSC), are remarkably similar: carbon ring structures decorated with sulfur atoms, without any additional moiety. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…325 Using molecular dynamics and metadynamics, Sugden et al demonstrated that while sulower has a number of stable low-energy crystal forms (including the experimental crystal), all 20 of the lowest structures of persulferated coronene became disordered in the dynamics simulations, consistent with its amorphous behavior experimentally. 326 A promising new, even simpler approach for landscape reduction based on the threshold method was demonstrated by Butler and Day. 327 They coarsely estimate the energy barriers and structural relationships between predicted polymorphs via Monte Carlo moves that translate or rotate molecules and/or deform the unit cell parameter, accepting only moves that stay below a given energy threshold.…”
Section: Predicting Solubility and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…325 Using molecular dynamics and metadynamics, Sugden et al demonstrated that while sulower has a number of stable low-energy crystal forms (including the experimental crystal), all 20 of the lowest structures of persulferated coronene became disordered in the dynamics simulations, consistent with its amorphous behavior experimentally. 326 A promising new, even simpler approach for landscape reduction based on the threshold method was demonstrated by Butler and Day. 327 They coarsely estimate the energy barriers and structural relationships between predicted polymorphs via Monte Carlo moves that translate or rotate molecules and/or deform the unit cell parameter, accepting only moves that stay below a given energy threshold.…”
Section: Predicting Solubility and Mechanical Propertiesmentioning
confidence: 99%
“… 325 Using molecular dynamics and metadynamics, Sugden et al demonstrated that while sulflower has a number of stable low-energy crystal forms (including the experimental crystal), all 20 of the lowest structures of persulferated coronene became disordered in the dynamics simulations, consistent with its amorphous behavior experimentally. 326 …”
Section: Selected Applications At the Frontiers Of Crystal Structure ...mentioning
confidence: 99%
“…However, the most developed methodology involves a series of molecular dynamics (MD) and enhanced sampling simulations to group the CSP structures into free energy clusters. [33][34][35][36][37][38][39][40] This method has a strong physical basis and has been successfully applied to a variety of systems. Nevertheless, the protocol has not become widely adopted primarily due to its complexity, both in the simulations and in the processing and analysis of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Methods based on arguments of crystallization kinetics ( 30 , 31 ) and packing similarity ( 32 ) have been proposed. However, the most developed methodology involves a series of molecular dynamics (MD) and enhanced sampling simulations to group the CSP structures into free energy clusters ( 33 40 ). This method has a strong physical basis and has been successfully applied to a variety of systems.…”
mentioning
confidence: 99%